Aplikasi Berbagai Media Tanam Terhadap Pertumbuhan Semai Cendana (Santalum album Linn) di Tempat Persemaian Permanen Fatukoa, Desa Naioni - Christoforus Januard Lepa; Mamie E. Pellondo’u; Norman P. L. B. Riwu Kaho (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2023)
Sandalwood is a type of plant native to Indonesia that grows endemic to several islands in the East Nusa Tenggara region. This study aims to determine the effect of planting media on the growth of sandalwood seedlings. This study used a completely randomized design (CRD) analysis with Duncan Multiple Range Test . Observations were made on the growth of height, diameter, number of leaves, fresh weight and dry weight of the seedlings. The results showed that the treatment of the growing media had a very significant effect on the height of the seedlings, and had a significant effect on the stem diameter and number of leaves, while it had no effects on the wet and dry weight. The best treatment was obtained from the M3 treatment (soil mixed with chicken faeces), which was shown with an average seedling height of 12.56 cm, a seedling diameter of 1.88 mm and a total of 13.8 leaves.